Footsteps - Tom Leader (Oz, 2018)
It’s fascinating to learn the stories of how people ended up in the work they do and why....and then how their work changed over their lives. More often than not relationships to mothers and fathers have a lot to do with it. Trying to please them, rebel against them, outdo them, live up to them, remember them. As a teenager, I wanted to write fiction and model myself after Hemingway. I thought I might be good at it and I knew my mother would be gratified, partly because of her own ambitions that weren’t realized.